Microscopic description of proton-induced spallation reactions with the constrained molecular dynamics (CoMD) model. (24th May 2019) - Assimakopoulou, A; Souliotis, G A; Bonasera, A; Botvina, A; Nicolis, N G; Veselsky, M
Abstract: We studied the complete dynamics of the proton-induced spallation process with the microscopic framework of the constrained molecular dynamics (CoMD) model. We performed calculations of proton-induced spallation reactions on 181 Ta, 208 Pb, and 238 U targets with the CoMD model and compared the results with a standard two-step approach based on an intranuclear cascade model followed by a statistical deexcitation model. The calculations were also compared with recent experimental data from the literature. Our calculations showed agreement with some aspects of the experimental data and suggest further improvements in the models. We point out that this CoMD study represents the first complete dynamical description of spallation reactions with a microscopic N-body approach and may lead to advancements in the physics-based modeling of the spallation process.